Technology-Based Integration to Develop Students’ Narrative Text - Bobby Pramjit Singh Dhillon; Bachrudin Musthafa; Yanti Wirza (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Improving students' skills in writing English is considered challenging for non-native students because of their lack of knowledge in building ideas, vocabularies, and the organization of the text. Therefore, this article aims to analyze and describe whether technology-based integration can develop students’ narrative writing. The method used to analyze the text was an experimental approach with sixty students taking Writing II subject at Nommensen University Pematangsiantar, Indonesia. Thirty students involved in the experimental group were provided with the technology-based environment (HyperStudio), while the other thirty students in the control group were not. The results of the study showed there was a significant improvement in the students’ narrative writing in the experimental group. The results of the study are expected to give great insights and knowledge for creative pedagogy in the classroom. However, the researcher suggests that future studies use a larger sample with a diverse range of learning styles, age groupings, and gender. In addition, future researchers should also look into the benefits of using HyperStudio across the curriculum in Indonesia, including science, social studies, history, geography, and other subjects.